2020
DOI: 10.1186/s12969-020-0408-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting referral of JIA patients to a tertiary level pediatric rheumatology center in North India: a retrospective cohort study

Abstract: Background: JIA studies demonstrate that there is a "window of opportunity" early in the disease course during which appropriate management improves outcomes. No data is available regarding patients' pathway, before first pediatric rheumatology (PR) evaluation in India, a country where health-care costs are self-paid by patients and where a significant shortage of pediatric rheumatologists (PRsts) is known. This study aimed to describe time from onset of symptoms to first PR visit of JIA patients to a tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
1
3
1
Order By: Relevance
“…Patients with JIA received the final diagnosis earlier compared to subjects with mechanical or functional disorders, at a median time of 3.9 months. This figure is consistent with previous studies, where the time from the onset of symptoms to JIA diagnosis ranged from 1.9 to 12 months, with a median of 4.6 months (Figure 1) [49][50][51][52][53][54][55][56][57][58][59][60][62][63][64][65][66]. To note, in our cohort, time to diagnosis varied significantly among JIA categories, with ERA patients obtaining a diagnosis after a median of 15 months, a significantly longer time than subjects with oligoarticular and polyarticular JIA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Patients with JIA received the final diagnosis earlier compared to subjects with mechanical or functional disorders, at a median time of 3.9 months. This figure is consistent with previous studies, where the time from the onset of symptoms to JIA diagnosis ranged from 1.9 to 12 months, with a median of 4.6 months (Figure 1) [49][50][51][52][53][54][55][56][57][58][59][60][62][63][64][65][66]. To note, in our cohort, time to diagnosis varied significantly among JIA categories, with ERA patients obtaining a diagnosis after a median of 15 months, a significantly longer time than subjects with oligoarticular and polyarticular JIA.…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, the few available studies analyzing differences among JIA subtypes evinced that ERA, together with psoriatic arthritis, is usually diagnosed later while oligoarticular JIA is typically recognized earlier (Figure 2 To note, in our cohort, time to diagnosis varied significantly among JIA categories, with ERA patients obtaining a diagnosis after a median of 15 months, a significantly longer time than subjects with oligoarticular and polyarticular JIA. Consistently, the few available studies analyzing differences among JIA subtypes evinced that ERA, together with psoriatic arthritis, is usually diagnosed later while oligoarticular JIA is typically recognized earlier (Figure 2) [49][50][51]58,60,65,66]. Before PR referral, JIA patients encountered more doctors than subjects with other diagnoses, but there was no firm evidence that they had been investigated with more radiological investigations and blood tests conducted than patients with different diagnoses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, the median time to first PR visit was short (2.4 months) compared to other studies [14][15][16][17][18][19][20][21][22][23][24][25] and close to the British guidelines [13] (children with suspected JIA are to be assessed by a PR team within 10 weeks of symptom onset). However, the data show a broad variability and an excessively long time to access PR centers for many patients (more than 6 months for 27% of patients, and more than 1 year for 14%) while it is known that a late referral can be associated with important damages (as well as articular as ophthalmologic) in most JIA subtypes.…”
Section: Discussioncontrasting
confidence: 57%
“…Despite guidelines, poor access for JIA patients to appropriate care remains a global issue. Literature reports give a median time to access the PRst of 3-10 months, with many medical stakeholders involved [14][15][16][17][18][19][20][21][22][23][24][25][26] and a broad variability in JIA subtypes [26]. It was found that some clinical characteristics and biological factors such as joint swelling, fever, and elevated C-reactive protein/ erythrocyte sedimentation rate were associated with a shorter time to first PR visit.…”
Section: Introductionmentioning
confidence: 99%